KINETIKA FERMENTASI ASAM LAKTAT DARI TEPUNG SORGUM MENGGUNAKAN YEAST DAN L.Plantarum - Istianah, Nur; Gunawan, Setyo (Fakultas Teknik, Universitas Brawijaya, 2017)
Sorghum fermentation was introduced by three of microbes which are dry baker’s yeast, L.Plantarum and the combination of them. Fermentor was operated at 37°C for 72 hrs. Inoculation of microbes was held after incubation period of 3-4 hrs. Those fermentation produce the different lactic acid and pH(p<0.05). L.Plantarum produced the highest lactic acid which was followed by pH changes. This fermentation gave the highest lactic acid yield of 85.01%(w/w) at cell yield of 0.14%(w/w). The production rate of fermentation by L.Plantarum was 0.306 g.h-1, maximum specific growth rate 1.5689 g.h-1, and Monod constat at 13.3262.